Analysis of Local Culture in English Learning Material in Junior High School - Fadhillah, Yuyun; Alifa, Yumna (English LAnguage Study and TEaching, 2024)
This research aims to analyze the extent to which local cultural elements are integrated into English language learning materials for junior high school. The focus of this study is on the English language book "English for Nusantara" designed for grade VIII SMP/MTs students. Utilizing a qualitative approach with a thematic content analysis design, the research examined various local cultural elements reflected in the English language learning materials. Data was collected through in-depth reading and analysis of the texts within the book. The research findings indicate the successful integration of five local cultural elements into the English language materials, such as local language, local traditions, local areas, local food, and folktales. This integration positively contributes to contextualizing English language learning for junior high school students, creating a learning experience that is more relevant to their cultural realities. The implications of these findings provide valuable guidance for the development of English language learning materials that are more contextual and aligned with the cultural needs of students at the junior high school level.